There was coordinated inauthentic user behavior in the COVID-19 German X-discourse, but did it really matter? - Sarhan, Habiba; Hegelich, Simon (Frontiers in Communication, 2025)
This study examines the role of coordinated inauthentic user behavior (CIUB) in the German COVID-19 discourse, focusing on the #nocovid hashtag. We analyze CIUB in relation to three dimensions of social media: communication, networks, and platforms. While our findings confirm the presence of coordinated behavior within the discourse, our analysis shows that CIUB itself did not significantly influence the debate. Instead, platform policies appear to have played a crucial role in shaping engagement by selectively amplifying or suppressing specific viewpoints. Using Granger causality analysis, we demonstrate that coordinated activity does not drive non-coordinated discourse. Conversely, an analysis of platform effects reveals that X’s algorithm systematically limited the visibility of anti-nocovid viewpoints. These findings highlight the need to reassess concerns about the influence of CIUB, shifting focus toward the role of platform policies in structuring online debates.